Poly(glycidyl methacrylate)/bacterial cellulose nanocomposites: preparation, characterization and post-modification - Faria, Marisa (2021)
Nanocomposites composed of poly(glycidyl methacrylate) (PGMA) and bacterial cellulose (BC) were prepared by the in-situ free radical polymerization of glycidyl methacrylate (GMA) inside the BC network. The resulting nanocomposites were characterized in terms of structure, morphology, water-uptake capacity, thermal stability and viscoelastic properties. The three-dimensional structure of BC endowed the nanocomposites with good thermal stability (up to 270 °C) and viscoelastic properties (minimum storage modulus = 80 MPa at 200 °C). In addition, the water-uptake and crystallinity decreased with the increasing content of the hydrophobic and amorphous PGMA matrix. These nanocomposites were then submitted to post-modification via acid-catalysed hydrolysis to convert the hydrophobic PGMA into the hydrophilic poly(glyceryl methacrylate) (PGOHMA) counterpart, which increased the hydrophilicity of the nanocomposites and consequently improved their water-uptake capacity. Besides, the post-modified nanocomposites maintained a good thermal stability (up to 250 °C), viscoelastic properties (minimum storage modulus = 171 MPa at 200 °C) and porous structure. In view of these results, the PGMA/BC nanocomposites can be used as functional hydrophobic nanocomposites for post-modification reactions, whereas the PGOHMA/BC nanocomposites might have potential for biomedical applications requiring hydrophilic, swellable and biocompatible materials.